Effect of recombinant human thrombopoietin on IL-2, IL-4 and platelet parameters in thrombocytopenic purpura: Effect of recombinant thrombopoietin on IL-2, IL-4 - Zhao, Meng; Liang, Xiaoyan; Chen, Chao; Du, Xin; Dang, Xiaowei (Cellular and Molecular Biology, 2023)
The objective of this study was to observe the effect of recombinant human thrombopoietin on IL-2, IL-4 and platelet parameters in thrombocytopenic purpura. For this purpose, a convenient sampling method was used to select 84 patients with thrombocytopenic purpura who visited the hospital from January 2018 to December 2022. The patients were divided into the norm group and rhTPO group with 42 cases each by random number table. The norm group was treated with routine treatment, while the rhTPO group was treated with recombinant thrombopoietin based on routine treatment. The changes in IL-2, IL-4, platelet parameters, immune recovery and treatment efficiency of the two groups were compared before and after treatment. Findings suggested that the levels of IL-2 and IL-4 in both groups decreased after treatment compared with those before treatment. However, the level of IL-2 in the rhTPO group after treatment was lower than that in the norm group, and the level of IL-4 in the rhTPO group after treatment was higher than that in the norm group (P<0.05). The levels of platelet parameters PLT and PCT in the two groups after treatment were higher than those before treatment, but the levels of PLT and PCT in the rhTPO group after treatment were higher than those in the norm group (P<0.05). The PLT of the rhTPO group was (69.57±6.73)×109/L after 7 days of treatment, which was higher than that in the norm group (62.05 ± 8.52)×109/L (P<0.05). The levels of PDW and MPV in the two groups after treatment decreased compared with those before treatment, but the levels of PDW and MPV in the rhTPO group after treatment were lower than those in the norm group (P<0.05). The overall immune recovery and treatment effectiveness of the rhTPO group were significantly better than those of the norm group. In summary, recombinant human thrombopoietin used in patients with thrombocytopenic purpura can maintain the balance between T cell activation and inhibition homeostasis, and promote faster recovery of platelet parameters.